PENERAPAN UPAH MINIMUM REGIONAL TAHUN 2016 DALAM MENENTUKAN TARIF JASA TEKNOLOGI DESAIN DULANG KERAMIK - I Nyoman Normal; Ni Nyoman Nurani (Forum Manajemen STIMI Handayani Denpasar, 2016)
The aims of this research that relate regional minimum wage 2016 intodetermine technology service rate ceramics coaster design were: (1) to know theinfluence of regional minimum wage to cost of goods manufactured; (2) to know thecomparisson of servive rate (cost price) year 2015 and 2016; and (3) to know theprofitability year 2015 and 2016. The research results shew that: (1) the addition ofregional minimum wage Denpasar Region can increase cost of good manufacturedceramics coaster design. (2) The comparisson of service rate (cost price) ceramiccoaster design in 2015 different with 2016. The comparisson of service rate ceramiccoaster design in 2016 to 2015 was 1,07; and (3) The addition of regional minimumwage Denpasar Region in 2016 can increase profitability ((Gross Profit Margin(GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM)) service rateceramic coaster design. The Gross Profit Margin (GPM), Operating Profit Margin(OPM), and Net Profit Margin (NPM)) in 2016 were Rp 2.348,14, Rp 1.174,07, andRp 1.018,33 each unit. It were mean that if the minimum wage of Denpasar regionincrease, so the profitability ((Gross Profit Margin (GPM, Operating Profit Margin(OPM), and Net Profit Margin (NPM)) tends will increase.